2016
DOI: 10.1016/j.jmaa.2016.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Robust recovery of stream of pulses using convex optimization

Abstract: This paper considers the problem of recovering the delays and amplitudes of a weighted superposition of pulses. This problem is motivated by a variety of applications, such as ultrasound and radar. We show that for univariate and bivariate stream of pulses, one can recover the delays and weights to any desired accuracy by solving a tractable convex optimization problem, provided that a pulse-dependent separation condition is satisfied. The main result of this paper states that the recovery is robust to additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 51 publications
3
94
0
Order By: Relevance
“…A consecutive paper [12] showed that the recovery is robust to noisy measurements. Similar results are given for support detection from low Fourier coefficients [4], [23], recovery of non-uniform splines from their projection onto spaces of algebraic polynomials [8], [18] and recovery of streams of pulses [6], [9]. (see also [17]).…”
Section: Introductionsupporting
confidence: 63%
“…A consecutive paper [12] showed that the recovery is robust to noisy measurements. Similar results are given for support detection from low Fourier coefficients [4], [23], recovery of non-uniform splines from their projection onto spaces of algebraic polynomials [8], [18] and recovery of streams of pulses [6], [9]. (see also [17]).…”
Section: Introductionsupporting
confidence: 63%
“…Our techniques are inspired by the deterministic certificate used to establish exact recovery of an atomic measure from low-pass measurements in [14]. Similarly, if the whole convolution K is assumed to be known, as in [5,6,54], a certificate can be built by interpolating the sign pattern with the convolution kernel in the same way. This polynomial is constructed via interpolation using a lowpass interpolation kernel with fast decay.…”
Section: Dual Certificatementioning
confidence: 99%
“…6 To define piecewise bounds that are valid on each U j , we maximize over the sets in the partition of OE .S; T /; .S; T / 2 , which contain points that satisfy the sample-separation condition in Definition 2.2. These bounds can be computed by interval arithmetic using the fact that the functions B .i / and W .i / can be expressed in terms of exponentials and polynomials.…”
Section: B5 Proof Of Lemma 37: Piecewise-constant Boundsmentioning
confidence: 99%
See 2 more Smart Citations